Neighborhood context and juvenile recidivism: a spatial analysis of organizations and reoffending risk - Thompson-Dyk, Kendra (Crime & delinquency, 2022)
Leveraging point-level spatial data from the Phoenix area, we consider the role of nearby organizations as contextual factors that amplify or reduce reoffending risk among juvenile offenders after court completion. Using survival models, we examine whether residential proximity to seven types of organizations impacts risk of recidivism, net of neighborhood disadvantage and offender characteristics. Aggregate neighborhood disadvantage was not associated with reoffending risk and organizational findings were mixed. Low-level offenders with more total organizations nearby had a higher risk of new property offenses, while the risk of drug and violent reoffending nearly doubled for diversion youth residing near police facilities or detention centers. Individual demographics and prior offense histories remained the strongest, most consistent predictors of juvenile recidivism